Hepatokine Pregnancy Zone Protein Governs the Diet‐Induced Thermogenesis Through Activating Brown Adipose Tissue - Jun Lin; Xiaoxiao Jiang; Meng Dong; Xiaomeng Liu; Qiwei Shen; Yuanyuan Huang; Hanlin Zhang; Rongcai Ye; Huiqiao Zhou; Chunlong Yan; Shouli Yuan; Xiangnan Wu; et al. (Advanced Science, 2021)
Abstract Intermittent fasting (IF), as a dietary intervention for weight loss, takes effects primarily through increasing energy expenditure. However, whether inter‐organ systems play a key role in IF remains unclear. Here, a novel hepatokine, pregnancy zone protein (PZP) is identified, which has significant induction during the refeeding stage of IF. Further, loss of function studies and protein therapeutic experiment in mice revealed that PZP promotes diet‐induced thermogenesis through activating brown adipose tissue (BAT). Mechanistically, circulating PZP can bind to cell surface glucose‐regulated protein of 78 kDa (GRP78) to promote uncoupling protein 1 (UCP1) expression via a p38 MAPK‐ATF2 signaling pathway in BAT. These studies illuminate a systemic regulation in which the IF promotes BAT thermogenesis through the endocrinal system and provide a novel potential target for treating obesity and related disorders.